O epigramach z „Żywotów Homera” słów kilka - Appel, Włodzimierz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
This short article aims at drawing attention to the Gelegenheitsdichtungen (occasional poetry) which, directly or indirectly, are identifed with epigrams in the preserved texts of Homer’s life. In this context it seems interesting that Homer’s epitaph, composed and inscribed in hexameters, is elegeion not epigramma.
Some words on epigrams from Homeris live
Keywords: Lives of Homer; Occasional poetry; Epigram and elegy